Tourism education in Singapore : an audit and analysis at post-secondary level. - Hugh Catlin. (2009)
The major problem confronting the tourism industry in Singapore is the dearth of skilled personnel to service it. The consequences of this problem are declining levels of service quality, negative impact on customer satisfaction and ultimately declining profitability. The solution to the problem requires a coordinated approach to education for tourism, an approach which is attuned to economic realities.